النصّ القرآني بين القراءات الحداثية المعاصرة وآليات علم أصول الفقه - همّال, الحاج (جامعة الوادي - University of Eloued, 2022)
يتناول هذا البحث بالتّحليل والمقارنة، أحقيّة آليات علم أصول الفقه بتفسير النصّ القرآني عن أيّ آليات أخرى في المعرفة الإسلامية، فضْلاً عن الآليات الّتي وظّفتها مدارس تحليل الخطاب لتفسير النّصوص المقدّسة، ممّا هو متداول باسم القراءات الحداثية المعاصرة. وقد تمّ الوصول إلى تأكيد أحقيّة علم أصول الفقه، بتفسير نصّ القرآن الكريم على جميع مدارس تحليل الخطاب في الفكر الغربي؛ ببيان ظروف ظهور هذه المدارس مع عرض قراءتين حداثيتين وتوجيه النّقد لهما، ثمّ إثبات أولوية أدوات علم أصول الفقه بتفسير النصّ القرآني، لاشتماله على منظومة معرفية متكاملة تتجاوز كلّ العلوم بما فيها العلوم المتّصلة بالقرآن الكريم؛ كعلوم القرآن وعلوم اللّغة العربية. وقد وظّف الباحث للوصول إلى النّتائج الّتي انتهى إليها أدوات المنهجين الوصفي والتّحليلي النّقدي، موافقا المعطى المعرفي الإسلامي، وهو سلامة نصوص القرآن الكريم من التّغيير وسلامة مضامينه من التأويل المتعسَّف أو المحتمل لخلاف ما أقرّته أدلّة الشّرع القطعية، مؤكّدًا أنّ كلمة الله تعالى الوحيدةَ الباقيةَ هي نصُّ القرآن الكريم وحده. Abstract : This research deals with analysis and comparison, the eligibility of the mechanisms of jurisprudence to interpret the Qur’anic text from any other mechanisms in Islamic knowledge, as well as the mechanisms employed by the discourse analysis schools to interpret the sacred texts, which is known as the contemporary modernist readings. Confirmation of the validity of the science of jurisprudence has been reached by interpreting the text of the Noble Qur’an on all schools of discourse analysis in Western thought; By explaining the circumstances of the emergence of these schools, then presenting two modernist readings by virtue of the preference of the local modernist elite to them about the mechanisms used in heritage, while directing criticism to them, so that the research moves to prove the priority of the tools of jurisprudence by interpreting the Qur’anic text over any Islamic cognitive tools, as it includes an integrated knowledge system. It transcends all sciences, including those related to the Holy Qur’an. Such as the sciences of the Qur’an and the sciences of the Arabic language
The Qur’anic text between contemporary modernist readings and the mechanisms of jurisprudence
مقال
Keywords: النصّ الأوّل ; النّصوص الثّانوية ; القراءة الحداثية المعاصرة ; تحليل الخطاب; the first text; secondary texts; contemporary modern reading; discourse analysis; semantics.